Posttranslational Regulation of Inflammasomes, Its Potential as Biomarkers and in the Identification of Novel Drugs Targets - Nanda, Sambit K.; Vollmer, Stefan; Perez-Oliva, Ana B. (Frontiers in Cell and Developmental Biology, 2022)
In this review, we have summarized classical post-translational modifications (PTMs) such as phosphorylation, ubiquitylation, and SUMOylation of the different components of one of the most studied NLRP3, and other emerging inflammasomes. We will highlight how the discovery of these modifications have provided mechanistic insight into the biology, function, and regulation of these multiprotein complexes not only in the context of the innate immune system but also in adaptive immunity, hematopoiesis, bone marrow transplantation, as well and their role in human diseases. We have also focused on less-studied modifications such as acetylation, ADP-ribosylation, nitrosylation and emphasized their relevance in the regulation of inflammasome complex formation. We have described disease-associated mutations affecting PTMs of inflammasome components. Finally, we have discussed how a deeper understanding of different PTMs can help the development of biomarkers and the identification of novel drug targets to treat diseases caused by the malfunctioning of inflammasomes.